2019
DOI: 10.1016/j.talanta.2018.11.094
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a global quantitative analysis methodology of tryptophan metabolites in mice using LC-MS

Abstract: In this study, we validated a method for quantifying 20 tryptophan (Trp) catabolites by liquid chromatography coupled with high resolution mass spectrometry (LC-HRMS) in 4 different matrices (urine, serum, intestinal contents and liver). The detection limit for all metabolites ranged between 0.015 and 11.25 nmol/L and the dynamic range of the calibration curves were adjusted to allow quantification of metabolites at endogenous levels. Matrix effects were evaluated using isotope labeled internal standards. Repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 26 publications
1
33
1
Order By: Relevance
“…Galla et al reported lower LOQs in serum for 3HKyn, XA, Kyna, and QA and higher LOQs for Trp and Kyn [29]. Lefèvre et al reported lower LOQs for serum when working with standards prepared in a solvent and a Q-Exactive mass spectrometer, whereas our values were estimated in the presence of a sample matrix [40]. Regarding the LOQs for peritoneal fluid, we did not find other LC-MS/MS methods reported for simultaneous Trp, NAm, and kynurenine determination.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Galla et al reported lower LOQs in serum for 3HKyn, XA, Kyna, and QA and higher LOQs for Trp and Kyn [29]. Lefèvre et al reported lower LOQs for serum when working with standards prepared in a solvent and a Q-Exactive mass spectrometer, whereas our values were estimated in the presence of a sample matrix [40]. Regarding the LOQs for peritoneal fluid, we did not find other LC-MS/MS methods reported for simultaneous Trp, NAm, and kynurenine determination.…”
Section: Discussioncontrasting
confidence: 50%
“…Therefore, multi-target analysis required appropriate adjustment of the conditions for the sample preparation protocol, estimation of linear ranges, and proper instrument settings. Although there are LC-MS/MS methods available for determining the levels of Trp and its metabolites in serum [24,25,28,29,40], we presented here an alternative and validated protocol using one internal standard (3NT) and a simple sample preparation workflow. Furthermore, we described a protocol for quantification of Trp, NAm, and the biologically important KP metabolites (QA, 3HKyn, 3HAA, AA, Kyn, Kyna, and XA) in peritoneal fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Trp and 20 Trp metabolites were quantified by liquid chromatography coupled with high resolution mass spectrometry from 3 different matrices: serum, feces and caecal content as previously described. 64 Among them, 4 metabolites were quantified for serotonin pathway: melatonine, N-acetyl-serotonine, serotonine, 5-OH-tryptophane. For the kynurenine pathway, 7 metabolites were measured 3-OH-kynurenine, picolinic acid, xanthurenic acid, quinolinic acid, kynurenine, kynurenic acid, 3-OH-anthranilic acid.…”
Section: Methodsmentioning
confidence: 99%
“…The LC-MS/MS procedure was performed as previously described. 61 Mass spectra were obtained using an 5500 Q-Trap (Sciex, Concord, Ontario, Canada) equipped with a TurboIon electrospray (ESI) interface set in the negative mode (needle voltage +5000 V) with nitrogen as the nebulizer set at 40 (arbitrary pressure unit given by the equipment provider). Curtain and heater pressures were set at 20 and 40, respectively (arbitrary unit).…”
Section: Metabolomic Analysis Of Fecal Samplesmentioning
confidence: 99%